2019
DOI: 10.1155/2019/6468729
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of Klotho in Patients with Chronic Kidney Disease: A Systematic Review and Meta-analysis

Abstract: Objective. The prognostic role of Klotho in patients with chronic kidney disease is still controversial. Therefore, we performed this meta-analysis to assess the relationship between the low sKlotho level and the risk of adverse kidney outcomes. Materials and Methods. We systematically searched medical databases, such as PubMed, Embase, and the Cochrane Library, for eligible publications regarding the relationship between the low sKlotho level and risk of adverse kidney outcomes. The quality of included studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 53 publications
1
27
0
1
Order By: Relevance
“…More importantly, in longitudinal human studies, downregulated sKlotho levels were shown to correlate strongly with rapid decline of estimated glomerular filtration rate or increase in mortality in CKD patients not undergoing dialysis [ 13 , 24 ]. All of the above studies support the notion that sKlotho may represent a novel potential prognostic biomarker for CKD patients [ 24 26 ]. This notion was also confirmed in our previous study [ 13 ].…”
Section: Discussionsupporting
confidence: 61%
“…More importantly, in longitudinal human studies, downregulated sKlotho levels were shown to correlate strongly with rapid decline of estimated glomerular filtration rate or increase in mortality in CKD patients not undergoing dialysis [ 13 , 24 ]. All of the above studies support the notion that sKlotho may represent a novel potential prognostic biomarker for CKD patients [ 24 26 ]. This notion was also confirmed in our previous study [ 13 ].…”
Section: Discussionsupporting
confidence: 61%
“…On the other hand, data on the relationship between klotho and kidney function are divergent. Some studies have shown that a decrease in serum klotho correlates with a reduction in renal function; nevertheless, in other studies, such a relationship has not been confirmed [237,238]. Similar controversies concern the link between klotho and both PTH and FGF-23 [187].…”
Section: Klotho Proteinmentioning
confidence: 99%
“…The association of FGF-23 with CKD progression has been previously reported; however, the number of studies investigating the prognostic value of sKlotho is very limited and their results are contradictory [19,20]. In a recent meta-analysis of 8 cohort studies, the relationship between sKlotho and risk of adverse renal outcomes in CKD patients was examined, finding out that low sKlotho is significantly associated with an increased risk of poor renal outcomes [31]. However, there are many conflicting results about Klotho that require further studies.…”
Section: Discussionmentioning
confidence: 99%